THE INFLUENCE OF SCHOOL LITERACY CULTURE THROUGH THE UTILIZATION OF READING CORNER ON STUDENTS' READING INTEREST - Faresha Fatikhani Nurhutamah; Dian Nuzulia Armariena; Marleni (Esteem Journal of English Education Study Programme, 2024)
This research is motivated by the low interest in reading among students caused by the lack of student attention to reading books in the reading corner, so that the reading corner looks unused and untidy, the lack of interesting reading material for students, so that students are not interested in reading, like chatting with friends, not paying attention when learning is taking place. This study aims to determine the effect of school literacy culture through the utilization of reading corners on student interest in reading at SD Negeri 69 Palembang. This research is a type of experimental research, namely the type of Quasi Experimental Design. The population and samples in this study were fourth grade students of SD Negeri 30 Palembang, totaling 16 students in the control class and 20 students in the experimental class. Data collection techniques in this study were observation, questionnaire and documentation. Data analysis techniques in this study include Normality Test, Homogeneity Test, Hypothesis Test. The results of hypothesis testing research show t count ≥ t table or 12.465 ≥ 2.048, so it can be concluded that H0 is rejected and Ha is accepted. This means that there is an influence of school literacy culture through the utilization of reading corners on student interest in reading at SD Negeri 69 Palembang.